Third Five Year Plan Progress Report 1961-66 Government of Rajasthan - Planning Commission (Planning Commission, 1961)
Prior to integration, Rajasthan was a conglomeration of nineteen princely slates and throe chiefships. varying in size, population, Political importance, administrative set up and stage of economic development. the process of integration which was started in 1948 was completed in 1956. when the State attained its present form. There were formidable problems of evolving new and adequate machinery of administration out of heterogeneous elements.
Directorate of Economics and Statistics Government of Rajasthan